A carnival of parting : the tales of King Bharthari and King Gopi Chand as sung and told by Madhu Natisar Nath of Ghatiyali, Rajasthan - Nath, Madhu Natisar (University of California Press, 1992)
Madhu Natisar Nath is a Rajasthani farmer with no formal schooling. He is also a singer, a musician, and a storyteller. At the center of A Carnival of Parting are Madhu Nath's oral performances of two linked tales about the legendary Indian kings, Bharthari of Ujjain and Gopi Chand of Bengal. Both characters, while still in their prime, leave thrones and families to be initiated as yogis - a process rich in adventure and melodrama, one that offers unique insights into popular Hinduism's view of world renunciation. Ann Grodzins Gold presents these living oral epic traditions as flowing narratives, transmitting to Western readers the interactive dimensions, the moods, and the pleasures of a village bard's performance. Three introductory chapters and an interpretive afterword, together with an appendix on the bard's language by David Magier, supply A Carnival of Parting with a richly detailed ethnographic, historical, and cultural backdrop. Gold gives a frank and engaging portrayal of the bard Madhu Nath and her work with him. She examines the Nath caste and their oral epic traditions as an important stream within North Indian Hinduism, showing how Madhu Nath's versions of Bharthari's and Gopi Chand's well-known tales surface as distinctive moments within complex legendary and historical currents. While embellished with miraculous displays of magical powers and evocative of profound spiritual dedication, the tales translated here are most profoundly concerned, Gold argues, with human rather than divine realities. In a compelling afterword, she highlights the thematic emphases on politics, love, and death. Although both narratives frequently invoke as ultimate authority the causal black hole of fate, they in no way acquiesce to fatalism. Madhu Nath's vital colloquial telling of Bharthari's and Gopi Chand's stories depicts renunciation as inevitable and interpersonal attachments as doomed, yet celebrates human existence as a "carnival of parting."